Android interactive word game in mother tongue for early childhood learners - Rosie Jane P. Siosan; Josephine R. Lavilla; Ma. Asuncion Christine V. Dequilla; Joel T. De Castro (Institute of Advanced Engineering and Science, 2021)
As ownership of mobile devices increases, the trend in the use of information and communications technology (ICT) in education also advances. In line with the mandate of the department of education to develop interactive strategies, this study aimed to design, develop, and evaluate an android interactive word game in Mother Tongue on the level of acceptability of the system based on content, instructional quality, technical quality, presentation and organization, and accuracy and up-to-dateness to address the gap for interactive mobile learning. This study used developmental and quasi-experimental research. The first phase of the study used developmental research to design, develop, and evaluate the acceptability of the android word game. The second phase of the study used quasi-experimental to evaluate the effectiveness of the developed android word game on the pupils' academic performance in mother tongue. The evaluation of the information technology (IT) experts resulted to a very acceptable rating for the android interactive word game, which was observed to be effective based on the higher post-test mean score or higher mean score of the pupils in the spelling skills after their exposure to the android interactive word game.